Fibroblast growth factor receptor: A systematic review and meta-analysis of prognostic value and therapeutic options in patients with urothelial bladder carcinoma - Kardoust Parizi, Mehdi; Margulis, Vitaly; Lotan, Yair; Mori, Keiichiro; Shariat, Shahrokh F (Urologic oncology, 2021)
To evaluate the oncologic prognostic value of fibroblast growth factor receptor (FGFR) and to assess the safety and efficacy of its inhibitors in patients with urothelial bladder carcinoma. A literature search using PubMed, Scopus, and Cochrane Library was conducted on June 2020 to identify relevant studies according to the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines. The pooled recurrence-free survival (RFS), progression-free survival (PFS), and cancer-specific survival (CSS) were calculated using a fixed or random effects model in patients with nonmuscle invasive bladder cancer (NMIBC). Overall, 62 studies comprising 9,229 patients were eligible and included in this systematic review and meta-analysis. Both FGFR3 mutation and protein overexpression were significantly associated with RFS, PFS, CSS, and overall survival. FGFR3 mutation was associated with worse RFS and better PFS (pooled hazard ratio: 1.30; 95% confidence interval: 1.08-1.57, and pooled hazard ratio: 0.62; 95% confidence interval: 0.42-0.92, respectively) in patients with NMIBC. In 11 studies reporting on the response to FGFR inhibitors, complete response rates, disease control rates, and overall response rate of 0% to 8%, 59.3% to 64.2%, and 40% were reported for dovitinib, infigratinib, and erdafitinib, respectively. Based on this study, FGFR3 mutation is a statistically significant prognostic factor for RFS in NMIBC. FGFR inhibitors have measurable benefit in patients with advanced and metastatic urothelial carcinoma. However, the results of ongoing RCTs and future well-designed studies are awaited to capture the differential biologic and clinical behavior of tumors harboring FGFR while helping to identify those who are most likely to benefit from FGFR inhibitors.
Keywords: prognóza; receptory fibroblastových růstových faktorů; Prognosis; karcinom z přechodných buněk; lidé; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; nádory močového měchýře; Receptors, Fibroblast Growth Factor; Humans